An Integrative Counseling Approach for African American Couples With Prostate Cancer. Issue 2 (10th October 2021) - Wood, Andrew W.; Martin, Jessica L.; Bruns, Kaitlyn
Abstract : The experiences of African American couples facing prostate cancer include cancer concerns that intersect with sexuality, older age, and culture. We provide a review of concerns and counseling strategies and present an integrative approach through a case study. Future research on testing such approaches is encouraged.